The Relationship between Polar Vortex and Ozone Depletion in the Antarctic Stratosphere during the Period 1979–2016 - Yu Zhang; Jing Li; Libo Zhou (Advances in Meteorology)
As the most prominent feature of the polar stratosphere, polar vortex results in widespread changes in the climate system, especially in the ozone variation. In this study, the linkage between polar vortex and ozone depletion in Antarctic stratosphere during the period 1979–2016 is investigated; we calculated the averaged total column ozone within the polar vortex based on the vortex edge (−28.8 PVU PV contour) instead of the geographical region defined by latitude and longitude. Results from the spatial patterns of ozone and polar vortex suggest that the morphological changes of polar vortex can impact the horizontal distribution of ozone and the ozone within the polar vortex experiences a severe depletion in spring. The negative relationship between ozone and polar vortex in terms of vortex area, strength, and breakup time is significant with the correlation coefficients of −0.57, −0.68, and −0.76, respectively. The breakup time of polar vortex plays an important role in the relation between polar vortex and ozone depletion with the highest-value correlation coefficient among three polar vortex parameters. Furthermore, the possible mechanism for this relationship is also discussed in this article.